Ravenna : capital of empire, crucible of Europe - Herrin, Judith (Princeton University Press, 2020)
At the end of the fourth century, as the power of Rome faded and Constantinople became the seat of empire, a new capital city was rising in the West. Here, in Ravenna on the coast of Italy, Arian Goths and Catholic Romans competed to produce an unrivaled concentration of buildings and astonishing mosaics. For three centuries, the city attracted scholars, lawyers, craftsmen, and religious luminaries, becoming a true cultural and political capital. Bringing this extraordinary history marvelously to life, Judith Herrin rewrites the history of East and West in the Mediterranean world before the rise of Islam and shows how, thanks to Byzantine influence, Ravenna played a crucial role in the development of medieval Christendom. Drawing on deep, original research, Herrin tells the personal stories of Ravenna while setting them in a sweeping synthesis of Mediterranean and Christian history. She narrates the lives of the Empress Galla Placidia and the Gothic king Theoderic and describes the achievements of an amazing cosmographer and a doctor who revived Greek medical knowledge in Italy, demolishing the idea that the West just descended into the medieval "Dark Ages." Beautifully illustrated and drawing on the latest archaeological findings, this monumental book provides a bold new interpretation of Ravenna's lasting influence on the culture of Europe and the West.
Keywords: Ravenna (Italy) -- History -- To 1500.; Ravenna (Italy) -- Church history.; Cities and towns -- Italy -- History -- To 1500.; Ravenna (Italy) -- Kings and rulers -- Biography.; Social history.; Social Conditions; Histoire sociale.; social history.; HISTORY -- Medieval.; Social history; Kings and rulers; Cities and towns; Italy; Italy -- Ravenna; To 1500; Arian Baptistry.; Byzantine architecture.; Church of San Vitale.; City of Mosaics.; Deborah Mauskopf Deliyannis.; Eternal Ravenna.; Europe's greatest cities.; Exarchate of Revenna.; From the Etruscans to the Venetians.; Galla Placidia Mausoleum.; Justinian mosaic.; Jutta Dresken-Weiland.; Mariëtte Verhoeven.; Massimiliano David.; Ravenna in Late Antiquity.; The Early Christian Monuments of Ravenna.; great cities of Europe.; medieval history.; mosaics of Ravenna.; mosaics of San Vitale.; where in Italy should I visit?.; Church history; Biographies; History